Properties of nanoclay PVA composites materials - Mohamed H. M. Ali; Mohamoud M. Kahder; Khalid A. Al-Saad; Saeed Al-Meer (QScience Connect, 2012)
Polyvinyl alcohol (PVA)/ Na-rich Montmorillonite (MMT) nanocomposites were prepared using solution method to create polymer-clay nanocomposite (PCN) material. The PCN material was studied using X-ray diffraction (XRD), demonstrating polymer-clay intercalation that has a high d-spacing (lower diffraction angles) in the PCN XRD pattern, compared to the pure MMT clay XRD pattern, which has a low d-spacing (high diffraction angles). The nano-scanning electron microscope (NSEM) was used to study the morphological image of the PVA, MMT and PCN materials. The results showed that intercalation that took place between the PVA and MMT produced the PCN material. The mechanical properties of the pure PVA and the intercalated polymer material were studied. It was found that the small amount of MMT clay made the tensile modulus and percentage of the total elongation of the nano-composite significantly higher than the pure PVA polymer value, due to polymer-clay intercalation. The thermal stability of the intercalated polymer has been studied using thermal analytical techniques such as thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The results showed that the PCN material is more thermally stable than the pure PVA polymer.